3, 19-diacetyl-14-deoxy-11,12-didehydroandrographolide (srs27) antagonises inflammatory response and oxidative stress in in vitro and in vivo asthma models - Lim, Chee Woei (2014)
Corticosteroids and non-steroidal anti-inflammatories are the most effective treatments for a variety of inflammatory conditions such as asthma. Steroids act by blocking transcription factors, such as nuclear factor (NF)-κB and activator protein (AP)-1 to down-regulate a vast array of pro-inflammatory genes, whereas NSAIDs specifically target cyclo-oxygenase (COX) activity to reduce prostaglandin production. However, the use of both types of drugs is associated with unwanted side effects, and a significant proportion of patients are steroid resistant. Thus, there is an urgent need to develop novel antiinflammatory drugs to replace or complement present day therapy. The bioactive compounds from the famous Asian herb Andrographis paniculata (known locally in Malaysia as Hempedu Bumi) have been studied for almost a century. The focus has been placed on the identification of antiinflammatory and anticancer agents. The herb contains two main diterpenoid constituents named andrographolide (AGP) and 14-deoxy-11,12 didehydroandrographolide (DDAG). AGP and DDAG were found to exhibit anti-asthma effects by inhibiting inflammatory responses in an allergic mouse asthma model. As such, both of them could act as novel replacement for current anti-inflammatory drugs. However, due to inadequacies of both compounds in terms of drug-like properties, DDAG analogues were semisynthesised to tackle these shortcomings. Among the analogues, 3,19-diacetyl-14-deoxy-11,12- didehydroandrographolide (SRS27) was proven to inhibit cysteinyl leukotriene (CysLT) and nitric oxide (NO) synthesis in mouse macrophages,like AGP. However, DDAG on the other hand, failed to exhibit such activity. SRS27 was less toxic compared with AGP, which suggests that a simple chemical modification of DDAG produces a compound with CysLT and NO inhibitory activity similar to AGP but maintained the toxicity profile similar to DDAG. It is interesting to note that other analogues such as SRS28, SRS49,SRS76 and SRS83 with chemical modifications on the same carbon numbers 3 and 19 of DDAG were unable to show inhibition of CysLT and NO synthesis. Consequently, the potential anti-inflammatory effect of SRS27 was investigated in ovalbumin (OVA)-induced mouse asthma model. The compound was administered in a prophylactic manner and showed a substantial decrease in asthma parameters. SRS27 at 3 mg/kg twice daily for three days consecutively significantly reduced OVA-induced total cell such as macrophages, eosinophils, lymphocytes and neutrophils, as well as inflammatory cytokines such as IL-4, IL-5, IL-13 and eotaxin in bronchoalveolar lavage (BAL) fluid. The compound also suppressed serum IgE production. In addition, SRS27 suppressed mucus hyper-secretion and expression of inflammatory mediators such as TNF-α, MCP-1, Muc5ac,RANTES, IL-33 and iNOS. Mechanistically, the compound inhibited lung NF-κB p65 nuclear translocation. In line with this observation, p65 NF-κB nuclear translocation was also found to be inhibited by the compound in A549 lung cancer cell line. Notably, this inhibition was not a result of cell toxicity as peripheral blood count in normal BALB/C mice treated with 3 mg/kg of SRS27 was not affected. The acute toxicity in mice further supported this idea, which indicated SRS27 is indeed a safe compound, just like DDAG. A pharmacokinetic study in Balb/C mice at 3 mg/kg single dose revealed SRS27 that had a relatively short half-life but was able to achieve a concentration range of 13- 19 μM concentration that could be related to in vitro anti-asthma activities. SRS27 is the first known DDAG derivative tested positive in a mouse asthma model and as such this compound could serve as a prototype and template for future improvement as a potential prophylactic agent to control asthma.